Leveraging AI for Social Impact in Environmental Sustainability - Farheen Siddiqui; Homa Rizvi; Dr. Yusuf Perwej; Shamim Ahmad; Dr. Nikhat Akhtar (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This essay presents a social media web application intended to encourage community involvement in environmental and social projects as well as sustainable development. The platform wants to inspire people to get involved in social work and make a good difference in their communities. Two important components are an online job board and a donation system that prioritizes providing goods over cash contributions, promoting both philanthropy and economic empowerment. Moreover, the application recognizes and honours those who exhibit outstanding social efforts, promoting a culture of generosity and group assistance. Furthermore, a complaint system helps people to quickly report environmental problems, which helps to keep the environment safe and clean. This project aims to foster a more sustainable and inclusive future for society by utilizing technology to inspire and mobilize action.